2014
DOI: 10.1021/jp502212n
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum and Intramolecular Hydrogen Bonding of 2-Isocyanoethanol (HOCH2CH2N≡C)

Abstract: The microwave spectrum of 2-isocyanoethanol (HOCH2CH2NC) has been investigated in the 12-120 GHz spectral range. The assignment of this spectrum was severely complicated by the rapid transformation of 2-isocyanoethanol into its isomer 2-oxazoline, which has a rich and strong spectrum. This process appeared both in a gold-plated microwave cell and in a brass cell and is presumed to be catalyzed by metals or traces of base. The spectrum of one conformer was ultimately assigned. This form is stabilized by an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Under these conditions, the vibrational spectrum becomes simpler and different conformers can be more easily identified and characterized. Microwave spectra were recorded at room temperature or somewhat below [ 24 , 25 , 26 , 27 ]. Gas-phase electron diffraction structure determinations, sometimes at two or three different temperatures, were performed in the range of 297–733 K [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the vibrational spectrum becomes simpler and different conformers can be more easily identified and characterized. Microwave spectra were recorded at room temperature or somewhat below [ 24 , 25 , 26 , 27 ]. Gas-phase electron diffraction structure determinations, sometimes at two or three different temperatures, were performed in the range of 297–733 K [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…2-NC ethanol (2-isocyanoethanol). Only gas-phase studies have been found for the molecule by Møllendal et al [ 26 ]. Out of five considered conformers, the OCCN gauche structure is the most stable with an (O)H…N distance of 256 pm.…”
Section: Conformational Equilibriamentioning
confidence: 99%
“…Much of our work has focused on weak proton donor groups. Recently, we reported gas-phase studies of alcohols, carboxylic acids, thiols, thiolcarboxylic acids, selenols, amines, amides, , and phosphines, where the said groups are proton donors in internal H bonds with acceptors such as the fluorine atom, ,,, the chlorine atom, ,,, π-electrons of triple bonds, ,,,, π-electrons of double bonds, ,,,, and Walsh pseudo-π electrons. ,, References of many of our earlier works are found in the cited literature as well as in reviews. …”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular hydrogen bonding has for a long time been a favorite research theme of the Oslo laboratory, and a number of hydrogen bonds with a wide variety of hydrogen donors and acceptors have been investigated over the years. In the past several years, we have reported microwave (MW) spectra of the following molecules having internal hydrogen bonds: 2-isocyanoethanol (HOCH 2 CH 2 NC), 2-aminopropionitrile (H 2 NCH(CH 3 )CN), (2-chloroethyl)amine (ClCH 2 CH 2 NH 2 ), (chloromethyl)phosphine (ClCH 2 PH 2 ), propargylselenol (HCCCH 2 SeH), 2-propene-1-selenol (H 2 CCHCH 2 SeH), 2,2,2-trifluoroethanethiol (CF 3 CH 2 SH), 3-butyne-1-selenol (HSeCH 2 CH 2 CCH), 4-pentyn-1-ol (HOCH 2 CH 2 CH 2 CCH), ( Z )-3-mercapto-2-propenenitrile (HSCHCHCN), ( Z )-3-amino-2-propenenitrile (H 2 NCHCHCN), 3-butyne-1-thiol (HSCH 2 CH 2 CCH), (methylenecyclopropyl)methanol (H 2 CC 3 H 3 CH 2 OH), 2-chloroacetamide (ClCH 2 CONH 2 ), and cyclopropylmethylselenol (C 3 H 5 CH 2 SeH) . References to earlier work by us and others are found in these papers as well as in several reviews. …”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 400 MHz) δ 2.80 (d, 1H, 4 J HH = 2.6 Hz, CCH), 4.27 (d, 1H, 3 J HH = 6.8 Hz, OH), 5.23 (dd, 1H,3 J HH = 6.8 Hz,4 J HH = 2.6 Hz, CHO) 13. C NMR (CDCl 3 , 100 MHz) δ 50.7 ( 1 J CH = 157.5 Hz (d), OCH), 75.3 ( 2 J CH = 51.3 Hz (d), CCH), 76.8 ( 1 J CH = 257.5 Hz (d), CCH), 115.8 (CN).…”
mentioning
confidence: 99%